(3GdJfXje GdbGfhfj ddegfj (B:s (3OQGSI ebGQfI aj fWGb GdCYeGd GdJLGQjI (B/s - (3GdJejej, CcQe eMeO MSjfs ((3HjQhJ(B: s (3efThQGJ GdMdHj GdMbhbjI(B, s, 2010)
(3GdJCUjd GdJCQjNj dacQI Gdegfj(B- (3eaghe Gdegfj hGdbjhO GdeaQhVI Ydjg(B- (3GdeQcR GdbGfhfj ddegfj(B- (3GdeSDhdjI GdeOfjI ddegfj(B.s
(3eQGLY U(B.263s
Keywords: (3GdCYeGd GdJLGQjIs; (3Gdegfs; (3bGfhf GdYed hGdYeGds